2022
DOI: 10.1146/annurev-astro-052920-104505
|View full text |Cite
|
Sign up to set email alerts
|

Spirals in Galaxies

Abstract: Spirals in galaxies have long been thought to be caused by gravitational instability in the stellar component of the disk, but discerning the precise mechanism had proved elusive. Tidal interactions, and perhaps bars, may provoke some spiral responses, but spirals in many galaxies must be self-excited. We survey the relevant observational data and aspects of disk dynamical theory. The origin of the recurring spiral patterns in simulations of isolated disk galaxies has recently become clear, and it is likely th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 225 publications
(301 reference statements)
0
32
0
1
Order By: Relevance
“…Yu & Ho (2020) suggest that in galaxies with small bulges, spiral patterns are instead produced by random gravitational instabilities in the disk. Models of spiral structure produced by self-gravity in isolated differentially rotating disks are able to reproduce the multiple short arm fragments seen in flocculent galaxies, supporting this interpretation (Sellwood 2011;Grand et al 2012;D'Onghia et al 2013;Dobbs et al 2018;Sellwood & Masters 2022).…”
Section: Spiral Patterns and Barsmentioning
confidence: 53%
See 2 more Smart Citations
“…Yu & Ho (2020) suggest that in galaxies with small bulges, spiral patterns are instead produced by random gravitational instabilities in the disk. Models of spiral structure produced by self-gravity in isolated differentially rotating disks are able to reproduce the multiple short arm fragments seen in flocculent galaxies, supporting this interpretation (Sellwood 2011;Grand et al 2012;D'Onghia et al 2013;Dobbs et al 2018;Sellwood & Masters 2022).…”
Section: Spiral Patterns and Barsmentioning
confidence: 53%
“…For galaxies with small bulges, Yu & Ho (2020) suggest that the spiral patterns are instead produced by random gravitational instabilities in the disk. Models of this process (Sellwood 2011;Grand et al 2012;D'Onghia et al 2013;Dobbs et al 2018;Sellwood & Masters 2022) produce multiple short arm fragments similar to those seen in flocculent galaxies. Flocculent galaxies tend to have smaller bulges Bittner et al 2017;Díaz-García et al 2019), consistent with this idea.…”
Section: F3 Number Of Arms Concentration and Environmentmentioning
confidence: 87%
See 1 more Smart Citation
“…It is to be hoped that the same mechanism also accounts for the origin of self-excited spiral patterns in galaxies, but supporting observational evidence for this, or any other suggested excitation mechanism for spirals in galaxies, remains flimsy. See Sellwood & Masters (2022) for a full review of both the observed properties of spirals in galaxies and theoretical ideas to account for them.…”
Section: Introductionmentioning
confidence: 99%
“…However the quiescent "basic state" they invoke for the disc is at variance with the unrelaxed phase space in the local disc of the Milky Way that was recently reported by from an actionangle analysis of Gaia DR2 data (Gaia collaboration 2018). Furthermore, this theory disregards the more vigorous insta-1 Reproduced as http://www.physics.rutgers.edu/∼sellwood/supp material.html, and in the supplementary material of Sellwood & Masters (2022).…”
Section: Introductionmentioning
confidence: 99%